26.2k views
5 votes
Please help!!!! 5 TIMES I HAVE ASKED! I need real help. I can not afford to fail

Please help!!!! 5 TIMES I HAVE ASKED! I need real help. I can not afford to fail-example-1

1 Answer

4 votes

Both are D

First one:

f(g(x)) =f(x^2+3) then you x^2+3 is the x you are going to introduce in the function f

f(x^2+3)= sqrroot(x^2+3-3)= sqrroot (x^2) =x

Second:

you need to leave x alone

y = 3x^2 +1

y-1 = 3x^2

(y-1)/3 = x^2

sqrroot ((y-1)/3) = x

sqrroot ((x-1)/3) = h^-1(x)

User Candy Chiu
by
5.7k points